Trade Openness and Economic Growth in Indonesia - Ifa, Khoirul; Yahdi, Moh. (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Economic growth and international trade are related to one another. International trade stimulates long-term economic growth. The more trade activities in a country, the more rapid economic growth; this trade is a key component of development in a country, its contribution is felt with the increasing economic growth in several countries. The purpose of this study looks at the impact of trade openness on economic growth in Indonesia in 1986-2017. This research is a quantitative study using time series data from 1986-2017, research data obtained from the world bank, data analysis techniques using the GMM method to see the impact of trade openness on economic growth. The test results using the Generalized Method of Moments analysis method show that all variables significantly influence the dynamics of economic growth in Indonesia. This result is proven by the t-statistic probability value, which shows a smaller value compared to the t-table value. Then the value also has a probability of less than α. It can be concluded that the variables of trade, FDI, inflation, and the number of workers have a significant effect on economic growth in Indonesia.